BANKING INTERMEDIATION PERFORMANCE, ASSET QUALITY AND EFFICIENCY ON PROFITABILITY (STUDY IN BANK TABUNGAN NEGARA (PERSERO), TBK. PERIOD 2010 – 2016 - BUCHORY, HERRY ACHMAD (International Journal of Psychosocial Rehabilitation, 2018)
This study is to analyze the effect of banking intermediation performance, assets quality, and efficiency on profitability. The indicator used for banking intermediation performance is a loan to deposit ratio (LDR); asset quality is Non Performing Loans (NPLs); efficiency with the ratio of operating expense to operating income (OEOI) while profitability with the return on assets (ROA). Descriptive and verificative methods were used in this study. The published financial statements of PT. BTN period 2010-2016 periods are data sources that are processed with multiple linear regression. The results showed that partially LDR had a positive and significant effect on ROA; NPLs have a negative but not significant effect on ROA, and OEOI has a negative and significant effect on ROA. Simultaneously LDR, NPLs and OEOI effect on ROA.